IMPLEMENTASI NAZHIR DAN AKTA WAKAF PADA KECAMATAN HUTA BARGOT KABUPATEN MANDAILING NATAL DITINJAU DARI KOMPILASI HUKUM ISLAM DAN UU NO 41 TAHUN 2004 - Ramadhan Sahmedi Siregar, Ahmad Rosidi, Nawir Yuslem, (AT-TAFAHUM: Journal of Islamic Law, 2017)
Abstract: Nadzir in compilation of Islamic Law and Law Number 41/2004 are very important, because, nadzir is the one who has the right to receive waqf when it is submitted and in the name of nadzir, waqf is registered. Third, Nadzir has function to administer, manage, develop, control, protect the properties of waqf, and to report the implementation of duties to BWI. The endowment deed evidence of an asset is endowment. Because of the Huta Bargot community did not know the provisions of nadzir and the endowment deed itself so that it formed into a habit. It categorized as urf sahih (habits that do not violate syari'ah).Keywords: waqf, nadzir, endowment deed, Huta Bargor sub districtPendahuluan